Classification of game meat species Springbok (Antidorcas marsupialis) and Blesbok (Damaliscus pygargus phillipsi) with NIR hyperspectral imaging - Makhubo, Qhakazile Angel (2020)
Thesis (MScFoodSc)--Stellenbosch University, 2020.